The Effect of Corporate Governance on Earnings Quality - Alwis, Dulangi (My University, 2025)
Purpose: The intention of the study is to explore the effect of corporate governance on earnings quality on Finnish active companies listed on Nasdaq Helsinki Stock Exchange. Design/ Methodology/ Approach: The study analyses the independence of the audit commit-tee, size of the board, and CEO duality as a measure of the corporate governance on total accruals as an estimation for earnings quality. The sample of the research constitutes 91 active Finnish companies listed on Nasdaq Helsinki Stock Exchange over the period of 7 years from 2017 to 2023. The data obtained from the secondary sources include the annuals re-ports of the respective companies. Findings: The results of the thesis reveal that there is a positive relationship between independence of the audit committee, size of the board, and CEO duality over the earnings quality which is statistically insignificant. Although there is a positive association between corporate governance and earnings quality, P value of the regression analysis suggests that the relationship is insignificant, hence rejecting the first hypothesis of corporate governance has a significant positive effect on earnings quality and accepts null hypothesis. Research Implications: Research shows that globally held assumptions like, strong governance structures enhance the earnings quality may not be compatible with the Finnish con-texts, shows traditional variables of corporate governance may not capture the influence on earnings quality in highly regulated and transparent market in Finland which may refine the existing commonly accepted assumptions in Nordic settings. Findings may lead to policymakers and regulators shifting their focus to evaluate the effectiveness of governance bodies rather than expand governance requirements. Practical Implication: When conducting research, use at least more than three independent variables to get a good result, which may help to run the dataset to a standard level by eliminating the variables which are not fit for the analysis. Originality/ Value: The research on the influence of corporate governance on earnings quality conduct for Finnish market for the most recent research period of 2017 to 2023. It contributes new insights by exploring an area that has limited scholarly attention in Finland. Moreover, this study helps to understand the global findings on this topic, also true in the Finnish contexts.
Keywords: reporting; quality; executive boards; Finland; financial statements; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance